Towards Quality Management Procedures in 3D Cadastre - Nenad Višnjevac; Mladen Šoškić; Rajica Mihajlović (ISPRS International Journal of Geo-Information, 2024)
The 3D cadastre presents a modern approach to the development of cadastral information systems, with the role of improving current cadastral systems and overcoming the challenges of a 2D-based approach. Technological advancements, standardization, and scientific research in recent decades have contributed to the development and definition of the 3D cadastre. This positioned the 3D cadastre as an integral part of the future of land administration. However, every country needs to define a solution for itself based on its own legal system and cadastral tradition, while at the same time relying on international standardization and research. Once a 3D cadastral system is developed, it is crucial to ensure the monitoring, evaluation, and maintenance of both the quality of the cadastral data and the system itself throughout its lifecycle. Since 3D cadastres involve geometric data, quality management procedures must address both geometric and alphanumeric data. In this paper, we analyze and present the quality management procedures that should be included during designing, implementing, and maintaining a 3D cadastral system. Some examples based on real cadastral data were used to emphasize the need for improvement in quality management. The presented quality management procedures require further development in order to meet country-specific requirements and to fully support the 3D cadastre information systems.